2014
DOI: 10.1007/s11357-014-9727-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise increases resistance to oxidative stress in young but not older adults

Abstract: A single bout of acute exercise increases oxidative stress and stimulates a transient increase in antioxidant enzymes. We asked whether this response would induce protection from a subsequent oxidative challenge, different from that of exercise, and whether the effects were affected by aging. We compared young (20±1 years, n=8) and older (58±6 years, n=9) healthy men and women. Resistance to oxidative stress was measured by the F 2 -isoprostane response to forearm ischemia/reperfusion (I/R) trial. Each partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
1
21
0
1
Order By: Relevance
“…In a similar study, a high fitness level group of older adults (66 years) had increased SOD and GPx both at rest and following an acute bout of acute exercise as compared to a low fitness level group (Bouzid, Hammouda, Matran, Robin, & Fabre, 2015). In addition, SOD activity in response to acute eccentric exercise was found to be significantly higher in young (20 years) compared to older adults (58 years) (Nordin, Done, & Traustadottir, 2014), suggesting that signal transduction in response to acute exercise may be impaired with aging. In the present study, due to the characteristics of the exercise bouts, it is more likely that the activity of SOD declined because ROS production was low (Di Meo & Venditti, 2001).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a similar study, a high fitness level group of older adults (66 years) had increased SOD and GPx both at rest and following an acute bout of acute exercise as compared to a low fitness level group (Bouzid, Hammouda, Matran, Robin, & Fabre, 2015). In addition, SOD activity in response to acute eccentric exercise was found to be significantly higher in young (20 years) compared to older adults (58 years) (Nordin, Done, & Traustadottir, 2014), suggesting that signal transduction in response to acute exercise may be impaired with aging. In the present study, due to the characteristics of the exercise bouts, it is more likely that the activity of SOD declined because ROS production was low (Di Meo & Venditti, 2001).…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, due to the characteristics of the exercise bouts, it is more likely that the activity of SOD declined because ROS production was low (Di Meo & Venditti, 2001). It has been hypothesized that repeated periods of oxidative stress, as seen with some forms of exercise, may be needed to increase resistance to oxidative stress in older individuals (Nordin et al, 2014). Furthermore, it has been shown that older adults who exercise regularly had a lower oxidative profile and better ability to resist to an oxidative challenge (Traustadottir et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al [172] provided evidence that an acute RE session upregulates systemic indices of oxidative stress and reduces the antioxidant capacity in elderly women, immediately after the exercise. However, it seems that an age-related effect may exists, as a previous study showed a significantly higher activation of SOD in young compared to older adults, in response to an acute exercise bout [229]. Thus, it has been proposed that signal transduction of acute exercise may be impaired with aging [229].…”
Section: Acute Resistance Exercisementioning
confidence: 99%
“…However, it seems that an age-related effect may exists, as a previous study showed a significantly higher activation of SOD in young compared to older adults, in response to an acute exercise bout [229]. Thus, it has been proposed that signal transduction of acute exercise may be impaired with aging [229].…”
Section: Acute Resistance Exercisementioning
confidence: 99%
“…Exercise therefore acts as a non-drug therapy and is able to maximize the effect of hypoglycemic drugs [16]. Moreover, acute exercise promotes other metabolic benefits such as lipemia reduction [17] and increases in antioxidant enzymes [18]. The cardioprotective effects of exercise, through their reduction in blood pressure and peripheral vascular resistance, are associated with better acute metabolic function after exercise [19].…”
Section: Introductionmentioning
confidence: 99%